The Effectiveness of Reading Encoding Annotating and Pondering Technique Toward Students’ Reading Comprehension at SMA Negeri 1 Sarudu Kab. Pasangkayu - Hasmiati, Hasmiati; Sunubi, Abdul Haris (Al-Iftah: Journal of Islamic studies and society, 2021)
Reading is one of the language skills that should be mastered by the students of Senior High School in learning English. However, the students of the eleventh graders of SMA Negeri 1 Sarudu Kab. Pasangkayu still find difficulties in understanding reading English text, especially in descriptive text. the objective of the research is to know the effectiveness REAP technique to improve students' reading comprehension. This research used A Quasi-Experimental design by two group pre-test post test design. The population was the eleventh grade students of SMA Negeri 1 Sarudu Kab. Pasangkayu in academic year 2020/2021 which consists of 6 classes. The sample ofthis research was 66 students of the class XI. MIA1 and MIA2. The technique of samplig was purposive sampling, and the data was analyzed by using SPSS computer software. The result calculation of mean score pre-test students in experiment class was 50.81 and control class was 41.21, while the post-test mean score in experiment class was 74.52 and the control class was 65.00.The result finding that SPSS output for independent sample t-test = 4.756 and sig (2-tailed) = 0.000. This out reveals that sig = 0.000 < p-value = 0.05. It showed that the alternative hypothesis (H1) is accepted, which the t-test value (4.756) was greater than t-table value (2,042).